Cough Diagnosis: Present and Future - E. S. Ovsyannikov; S. N. Аvdeev; A. V. Budnevskiy; E. S. Drobyshevа (Туберкулез и болезни лёгких)
Chronic cough is a common symptom of numerous diseases occurring in about 10% of general population. The number of cough impulses over a period of time is an objective marker of cough severity. Cough frequency is now considered the primary endpoint in studies of the effectiveness of cough suppressants, as a factor contributing to the spread of tuberculosis, and as one of the indicators of patient stabilization during exacerbations of chronic obstructive pulmonary disease. The review discusses data from 60 literature sources on the principles of automatic cough impulses counting, methods used for objective cough assessment, and forecasts for future development in this field.